2022
DOI: 10.3390/ijerph192114240
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on the Prevalence of Depressive Symptoms and Its Associated Sociodemographic Factors in Peru during the COVID-19 Pandemic

Abstract: The present study aims to analyze the prevalence of depressive symptoms and its sociodemographic-associated factors in Peruvian adults. Data was extracted from a nation-wide representative survey in which depression symptoms were measured with the PHQ-9 and sociodemographic information was extracted from household data. Depression severity rates were estimated for each symptom, and responses were modeled through the Rating Scale Model to obtain a depression measure used as dependent variable on a Generalized M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…We recognize that this prevalence estimate was determined using a liberal PHQ-9 cutoff score of 5. Nonetheless, our prevalence estimate is much higher than that recently reported in the general Peruvian population during the pandemic period (~20%) (Zegarra-López et al, 2022). Our estimate is consistent with the pooled depressive symptom prevalence estimate among persons with TB (Duko et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…We recognize that this prevalence estimate was determined using a liberal PHQ-9 cutoff score of 5. Nonetheless, our prevalence estimate is much higher than that recently reported in the general Peruvian population during the pandemic period (~20%) (Zegarra-López et al, 2022). Our estimate is consistent with the pooled depressive symptom prevalence estimate among persons with TB (Duko et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…In the Peruvian context, depression among elderly people is a signi cant public health issue. Studies conducted in the country have revealed that the prevalence of depressive symptoms in this population varies from 10.8% to 40.7% [9], [10], [11], [12], [13], [14]. This wide range of prevalence can be attributed to differences in study methodologies and the characteristics of the populations studied.…”
Section: Introductionmentioning
confidence: 93%
“…These additions contributed to an increase in the prevalence of depression up to seven times worldwide (Bueno-Notivol et al, 2021), mainly affecting those who were quarantined alone or whose family or close friends were isolated in some way (Lei et al, 2020). Therefore, the COVID-19 pandemic exacerbated depressive symptoms in several sociodemographic groups, resulting in the necessity of an interventional approach adapted to the specific needs of each population, especially one such as the Peruvian population, which is characterized by socioeconomic challenges including poverty and the presence of vulnerable groups (Zegarra-López et al, 2022).…”
Section: Introductionmentioning
confidence: 99%